Multiple virus infections on Heterobasidion sp. Issue 2 (February 2020) - Hantula, Jarkko; Mäkelä, Salla; Xu, Ping; Brusila, Veera; Nuorteva, Heikki; Kashif, Muhammad; Hyder, Rafiqul; Vainio, Eeva J.
Abstract: Heterobasidion viruses have previously been shown to affect each other's transmission and phenotypic effects on their hosts in a complex way. In this work, Heterobasidion parviporum strains hosting five coinfecting viruses simultaneously were constructed and used as donors in transmission experiments. They showed that viruses move more frequently between the mycelia of the same species than between the mycelia of H. parviporum and H eterobasidion annosum . One of the strains was used to show that coinfection of five viruses is relatively unstable in a natural environment and analyses of the growth rate and competitive ability of Heterobasidion strains hosting various virus combinations revealed that viral effects are not additive. The results also supported the view that the transmission of the promising virocontrol agent HetPV13-an1 may be enhanced by coinfecting viruses in the donor mycelium. However, its detrimental effects may be blocked by the presence of other viruses in the same mycelium. Repositories: GenBank accession number MN058080. Highlights: Heterobasidion parviporum strains with five simultaneous virus infections were constructed. Viruses move more frequently between the mycelia of the same species than between the mycelia of H. parviporum and H eterobasidion annosum . Transmission of the promising virocontrol agent HetPV13-an1 may be enhanced by co-infecting viruses in the donor mycelium. Viral effects on the host phenotype may be affected by the presence of other viruses in the same mycelium.